Extreme thrombocytosis in traumatic amputee and role of thromboembolism prophylaxis: a case report - Sharma, Swati; Gunjiganvi, Mallikarjun; Sharma, Pulak; Bhalchandra, Awale R. (International Journal of Research in Medical Sciences, 2023)
Platelets are the smallest blood component produced in the bone marrow that plays a fundamental role in the blood clotting process. A normal platelet count applicable to all adults is 150 to 400×109/l. Thrombocytosis develops when the platelet count exceeds 450×109/l. Thrombocytosis is classified into primary thrombocytosis and secondary (or extreme) thrombocytosis. Primary thrombocytosis is a chronic myeloproliferative disorder in which sustained megakaryocyte proliferation leads to an increase in the number of circulating platelets. Extreme thrombocytosis or reactive thrombocytosis, is defined as abnormally high platelet count in the absence of chronic myeloproliferative disease, secondary to an underlying events, disease, or the use of certain medications. Causes of reactive thrombocytosis include acute blood loss, acute infection, amputation, iron deficiency, asplenia, cancer, chronic inflammatory or infectious diseases. Secondary thrombocytosis resolves when the underlying event is managed. Extreme thrombocytosis may result in thromboembolic episode such as mesenteric vein thrombosis, pulmonary embolism and acute myocardial infarction. In patients who survive after trauma the platelet count displays a bimodal response with an initial decrease below baseline values, followed by an increase above the normal range after 1 week. We report a similar experience of a trauma patient with reactive thrombocytosis and discussion on importance of thromboprophylaxis.